A DNA–Azobenzene Nanopump Fueled by Upconversion Luminescence for Controllable Intracellular Drug Release. Issue 50 (24th October 2019) - Zhang, Yue; Zhang, Yue; Song, Guobin; He, Yuling; Zhang, Xiaobo; Liu, Ying; Ju, Huangxian
Abstract: Stimulus‐responsive drug release possesses considerable significance in cancer therapy. This work reports an upconversion‐luminescence‐fueled DNA–azobenzene nanopump for rapid and efficient drug release. The nanopump is constructed by assembling the azobenzene‐functionalized DNA strands on upconversion nanoparticles (UCNPs). Doxorubicin (DOX) is loaded in the nanopump by intercalation in the DNA helix. Under NIR light, the UCNPs emit both UV and visible photons to fuel the continuous photoisomerization of azo, which acts as an impeller pump to trigger cyclic DNA hybridization and dehybridization for controllable DOX release. In a relatively short period, this system demonstrates 86.7 % DOX release. By assembling HIV‐1 TAT peptide and hyaluronic acid on the system, targeting of the cancer‐cell nucleus is achieved for perinuclear aggregation of DOX and enhanced anticancer therapy. This highly effective drug delivery nanopump could contribute to chemotherapy development. Abstract : A DNA nanopump is produced with azobenzene‐functionalized DNA strands for efficient and controllable drug release through the photoisomerization of azobenzene fueled by the simultaneous UV and visible‐light emissions of upconversion nanoparticles (UCNPs) under NIR irradiation. This triggers the release of an anticancer drug and enhances anticancer therapy.